Discourse - Cook, Guy (Oxford University Press, 1989)
This book shows how discourse analysis - the study of spoken and written languages in its social and psychological context - can provide important insignts for the language teacher. It explains the relevant theory and applies it to classroom activities designed to improve students' discourse skills.